International Comparisons of Sectoral Energy- and Labour-Productivity Performance: Stylised Facts and Decomposition of Trends - Peter Mulder; Henri L.F. de Groot (Tinbergen Institute, 2004)
This paper addresses the interplay between economic growth, energy use, change in sectoral composition and technological change, by exploring trends in energy- and labour productivity development for 14 OECD countries and four sectors over the period 1970-1997. A cross-country decomposition analysis reveals that in some countries structural changes contributed considerably to macroeconomic energy-productivity growth while in other countries they partly offset energy-efficiency improvements. In contrast, structural changes only play a minor role in explaining macroeconomic labour-productivity developments. We also find labour productivity growth to be higher on average than energy productivity growth. Over time, this bias towards labour productivity growth is increasing in Transport, Agriculture and Manufacturing, while it is decreasing in Services.
Keywords: O13; O47; O5; Q43; 330; energy productivity; labour productivity; convergence; sectoral analysis; decomposition analysis; Energiekonsum; Produktivität; Arbeitsproduktivität; Branche; OECD-Staaten